Transglutaminase-Catalyzed Bottom-Up Synthesis of Polymer Hydrogel - Lai, Enping; Bao, Binyu; Zhu, Yifei; Lin, Haitao (Frontiers in Bioengineering and Biotechnology, 2022)
Enzyme catalysis has attracted increasing attention for application in the synthesis of polymer hydrogel due to the eco-friendly process and the devisable catalytic reaction. Moreover, bottom-up approaches combining enzyme catalysts and molecular self-assembly have been explored for synthesizing hydrogel with complex architectures. An enzyme widely distributed in nature, transglutaminase (TGase) has been confirmed to catalyse the formation of isopeptide bonds between proteins, which can effectively improve the gelation of proteins. In this mini-review, TGase-catalysed synthesis of polymer hydrogel, including fibrin hydrogel, polyethylene glycol hydrogels, soy protein hydrogels, collagen hydrogels, gelatin hydrogels and hyaluronan hydrogels, has been reviewed in detail. The catalytic process and gel formation mechanism by TGase have also been considered. Furthermore, future perspectives and challenges in the preparation of polymer hydrogel by TGase are also highlighted.